2008
DOI: 10.1007/s10681-008-9825-z
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative trait locus on chromosome 5B controls resistance of Triticum turgidum (L.) var. diccocoides to Stagonospora nodorum blotch

Abstract: Stagonospora nodorum blotch (SNB) is an important foliar disease of durum wheat (Triticum turgidum var. durum) worldwide. The combined eVects of SNB and tan spot, considered as components of the leaf spotting disease complex, result in signiWcant damage to wheat production in the northern Great Plains of North America. The main objective of this study was the genetic analysis of resistance to SNB caused by Phaeosphaeria nodorum in tetraploid wheat, and its association with tan spot caused by Pyrenophora tritic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Tsn1 has been postulated to govern sensitivity to both toxins, and therefore serves as a major determinant for susceptibility to both Stagonospora nodorum blotch and tan spot (Liu et al 2006). However, Gonzalez-Hernandez et al (2009) reported a QTL proximal to Tsn1 in durum wheat and indicated that resistance to each disease was controlled by different but linked locus. Graminin A is a toxic compound produced by C. gramineum that has been implicated in the proliferation and development of the fungus in wheat (Creatura et al 1981;Kobayashi and Ui 1979;Rahman et al 2001;Van Wert et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Tsn1 has been postulated to govern sensitivity to both toxins, and therefore serves as a major determinant for susceptibility to both Stagonospora nodorum blotch and tan spot (Liu et al 2006). However, Gonzalez-Hernandez et al (2009) reported a QTL proximal to Tsn1 in durum wheat and indicated that resistance to each disease was controlled by different but linked locus. Graminin A is a toxic compound produced by C. gramineum that has been implicated in the proliferation and development of the fungus in wheat (Creatura et al 1981;Kobayashi and Ui 1979;Rahman et al 2001;Van Wert et al 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In a durum wheat population segregating for only chromosome 5B (including Tsn1), Gonzalez-Hernandez et al (2008) reported that the ToxA-Tsn1 interaction was not a significant factor in the development of SNB when they evaluated the population with the S. nodorum isolate Sn2000. However, we evaluated the same population with the same S. nodorum isolate and found that the ToxA-Tsn1 interaction was the only factor governing reaction to SNB, and the interaction explained 95% of the variation indicating that the ToxA-Tsn1 interaction is important for disease development in common wheat as well as durum wheat .…”
Section: Sntoxa -Tsn1mentioning
confidence: 99%
“…Complex quantitative inheritance ( Dubin and Rajaram, 1996 ; Joshi et al, 2004b ; Kumar et al, 2015b ) of SB resistance in wheat has slowed the progress in breeding for SB resistance. Many studies, using methods of both bi-parental mapping and association mapping (AM) have reported several SB resistance QTLs on chromosome 1A, 1B, 2A, 2B, 2D, 3B, 5A, 5B, 6B, 6D, 7A, 7B, and 7D ( Neupane et al, 2007 ; Sharma et al, 2007a ; Gonzalez-Hernandez et al, 2009 ; Kumar et al, 2009 , 2010 , 2015a , 2017 ; Adhikari et al, 2012 ; Lillemo et al, 2013 ; Zhuang et al, 2013 ; Gurung et al, 2014 ; Zhu et al, 2014 ; Lu et al, 2016 ; Zhang et al, 2015 ; Gupta et al, 2018 ). However, only three major QTLs designated as Sb1 on 7D ( Lillemo et al, 2013 ), Sb2 on 5B ( Kumar et al, 2015a ), and Sb3 on 3B ( Lu et al, 2016 ) are well described.…”
Section: Introductionmentioning
confidence: 99%